A economia política do governo Fernando Henrique Cardoso: neoliberalismo e dependência - Dias, Raul Costa de Oliveira (2019)
It is not possible to analyze any period of the political history of a nation without considering the theoretical and ideological influences behind the political decisions of a ruler. this dissertation, took off the effort to analyze the government of Fernando Henrique Cardoso (FHC) throughout its two terms, drawing a parallel with its main work Dependência e desenvolvimento – ensaios de interpretação sociológica; of the conception of Neoliberalismo formulated by Hayek and; of the vision about the internationalization of the economy as seen in Gustavo Franco. To counter the vision about dependence of Fernando Henrique Cardoso and Enzo Faletto, we revisit the work of Rui Mauro Marini, Dialética da dependência, and the writings of Aníbal Quijano on patterns of power in Latin America and Polo marginal y mano de obra marginal. We used data from the main organs of the Brazilian State to demonstrate the deepening of the level of dependence of the Brazilian economy based on the political decisions of the FHC government. We conclude that the policies of the government of Fernando Henrique Cardoso were aligned with a theory of dependence that does not seek the emancipation of the country